2016
DOI: 10.1016/j.joa.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the measured pre‐ejection periods and left ventricular ejection times between echocardiography and impedance cardiography for optimizing cardiac resynchronization therapy

Abstract: BackgroundThe pre-ejection period (PEP) and left ventricular ejection time (LVET) are easily measured by impedance cardiography (ICG). We hypothesized that the PEP/LVET measured by ICG would correlate with that measured by echocardiography, and that PEP/LVET measured by ICG would be useful for cardiac resynchronization therapy (CRT) optimization.MethodsNewly CRT implanted patients were optimized by echocardiography. The PEP/LVET was measured by echocardiography and ICG in two different settings: optimized sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Echocardiography is a standard modality extensively used in clinical settings for a variety of diagnostic purposes. However, its accuracy in finding the exact instant of valve opening or closing, besides being affected by noise and operator variability, as mentioned in the background section, it is also limited by the resolution of the captured frame and its poor synchrony with the ECG (Noda et al, 2017). To overcome these imprecisions, we proposed a new protocol for recording and labeling the echocardiogram images by performing a multimodal echocardiographic procedure and considering time windows for the assessment of the valve openings and closures.…”
Section: Methodsmentioning
confidence: 99%
“…Echocardiography is a standard modality extensively used in clinical settings for a variety of diagnostic purposes. However, its accuracy in finding the exact instant of valve opening or closing, besides being affected by noise and operator variability, as mentioned in the background section, it is also limited by the resolution of the captured frame and its poor synchrony with the ECG (Noda et al, 2017). To overcome these imprecisions, we proposed a new protocol for recording and labeling the echocardiogram images by performing a multimodal echocardiographic procedure and considering time windows for the assessment of the valve openings and closures.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Seery et al showed that PEP can be calculated using the R-wave instead of the Q-wave [ 15 ]. PEP can be considered as a measure of left ventricular function, as it reflects changes in the contractility of myocardium, left ventricular end-diastolic volume, and aortic diastolic pressure [ 13 , 16 18 ]. In patients with diabetic chronic kidney disease, fluid overload is a marker for left ventricular systolic dysfunction and is associated with the ratio of brachial PEP and brachial ejection time [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are other optimization methods which could be used in combination with echocardiography. Noda et al reported that PEP/left ventricular ejection time (LVET) calculations by impedance cardiography (ICG) and echocardiography were positively correlated [ 56 ]. Thus, ICG could be useful in combination with echocardiography for CRT optimization.…”
Section: Resultsmentioning
confidence: 99%